Endovascular Treatment of Intracranial Artery Dissection: Clinical and Angiographic Follow-Up - Reza Mohammadian; Ali Akbar Taheraghdam; Ehsan Sharifipour; Reza Mansourizadeh; Ali Pashapour; Mohammad Shimia; Ghaffar Shokouhi; Moslem shakeri; Ali Hashemzadeh (Neurology Research International)
Background. Intracranial artery dissections are rare and many controversies exist about treatment options. The aim of this study was to evaluate the efficacy and safety of the endovascular approach in patients with an intracranial dissection presenting with different symptoms. Methods. We prospectively evaluated the clinical features and treatment outcomes of 30 patients who had angiographically confirmed nontraumatic intracranial dissections over 4 years. Patients were followed up for 17 months, and their final outcomes were assessed by the modified Rankin Score (mRS) and angiography. Results. Sixteen (53.3%) patients had a dissection of the anterior circulation, whereas 14 (46.7%) had a posterior circulation dissection. Overall, 83.3% of the patients suffered a subarachnoid hemorrhage (SAH). Grade IV Hunt and Hess score was seen in 32% of the SAH presenting cases. Parent artery occlusion (PAO) with coil embolization was used in 70% of the cases. The prevalence of overall procedural complications was 23.3%, and all were completely resolved at the end of follow-up. No evidence of in-stent occlusion/stenosis or rebleeding was observed in our cases during follow-up. Angiography results improved more frequently in the PAO with coil embolization group (100%) than in the stent-only-treated group (88.9%) (P=0.310) and the unruptured dissection group (5/5, 100%) in comparison with the group that presented with SAH (95.8%) (P=0.833). Conclusion. Favorable outcomes were achieved following an endovascular approach for symptomatic ruptured or unruptured dissecting aneurysms. However, the long-term efficacy and durability of these procedures remain to be determined in a larger series.